Antioxidant and Hypoglycemic Effects of Momordica cochinchinensis Spreng: (Gac) Aril Extract on Reproductive Damages in Streptozotocin (STZ)-Induced Hyperglycemia Mice - Sampannang,Apichakan (Sociedad Chilena de Anatomía, 2017)
The aim of present study was to investigate the effect of Momordica cochinchinensis (Gag) aril (GA) aqueous extract on male reproductive system of streptozotocin (STZ)-induced hyperglycemia (HG) mice. GA were extracted with distilled water (DW) and analyzed for in vitro antioxidant capacities. ICR male mice were divided into 7 groups: 1) control, 2) DW, 3) GA 1000 mg/kg BW, 4) HG, 5) HG + glibenclamide, 6 and 7) HG + GA 500 and 1000 mg/kg BW respectively (7 mice/ group). In HG groups, mice were induced by STZ at single dose (150 mg/kg BW). They were treated for consecutive 35 days. All groups were compared for blood glucose levels, weights and histopathologies of reproductive organs, sperm concentration including testicular tyrosine phosphorylation protein patterns by Immuno-Western blotting. The results showed that GA processed antioxidant activities and could significantly decrease blood glucose levels and increase sperm concentration in HG mice. Moreover, GA could change the density of a testicular 70 kDa protein in HG-GA groups. In conclusion, GA extract could improve hyperglycemia and male reproductive damages in STZ-induced HG mice.